Why do we take drugs?: From the drug-reinforcement theory to a novel concept of drug instrumentalization - Spanagel, Rainer (Behavioral and brain sciences, 2011)
The drug-reinforcement theory explains why humans get engaged in drug taking behavior. This theory posits that drugs of abuse serve as biological rewards by activating the reinforcement system. Although from a psychological and neurobiological perspective this theory is extremely helpful, it does not tell us about the drug-taking motives and motivation of an individual. The definition of drug instrumentalization goals will improve our understanding of individual drug-taking profiles.
Gesehen am 19.10.2022